Negative electrode active material, and electrochemical device and electronic device using the same

By optimizing the graphitization degree, crystal structure and particle size distribution of the negative electrode active material, combined with appropriate surface density and porosity, the problem of insufficient energy density and cycling characteristics of lithium-ion batteries is solved, and a significant improvement in battery performance is achieved.

JP7627297B2Active Publication Date: 2025-02-05NINGDE AMPEREX TECHNOLOGY LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023045559
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2025-02-05
Estimated Expiration
2040-06-04

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have shortcomings in energy density, cycle characteristics and rate characteristics, and it is necessary to improve the negative electrode active material to improve its performance.

Method used

Carbon materials within a specific range are used as the negative electrode active material, and the performance of the negative electrode active material is optimized by controlling the graphitization degree (GR/K) and crystal structure (LC/S) and particle size distribution (DV10/DV90) of the carbon material, combined with appropriate surface density, compaction density and porosity to improve the energy density, cycle characteristics and rate characteristics of the battery.

Benefits of technology

It significantly improves the energy density, circulation characteristics and rate characteristics of lithium-ion batteries, reduces the cycle attenuation and lithium dendrites of lithium-ion batteries, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627297000003
    Figure 0007627297000003
  • Figure 0007627297000004
    Figure 0007627297000004
  • Figure 0007627297000005
    Figure 0007627297000005
Patent Text Reader

Abstract

SUMMARY OF THE INVENTION Embodiments of the present invention solve, at least in part, at least one problem in the related art by providing negative electrode active materials and electrochemical and electronic devices using same. [Solution] The present invention relates to an anode active material and an electrochemical device and an electronic device using the same. More specifically, the present invention provides an anode active material containing a carbon material, and the carbon material has a specific peak intensity ratio K and a ratio of the degree of graphitization Gr to K within a specific range. The anode active material of the present invention can significantly improve the energy density, cycle characteristics, and rate characteristics of an electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage, and more particularly, to a negative electrode active material, and an electrochemical device and an electronic device using the same.

Background Art

[0002] Electrochemical devices (for example, lithium-ion batteries) are widely used because they are environmentally friendly and have advantages such as high operating voltage, large specific capacity, and long cycle life, and have become the most promising new type of green chemical power source in the current world. Small lithium-ion batteries are usually used as a power source for driving portable electronic communication devices (for example, camcorders, mobile phones, or notebook personal computers, etc.), especially for driving high-performance portable devices. Medium and large lithium-ion batteries with high output characteristics are developed for application to electric vehicles (EV) and large-scale energy storage systems (ESS). With the widespread use of lithium-ion batteries, their energy density, cycle characteristics, and rate characteristics have become technical problems that need to be solved urgently. Improving the active material material in the electrode sheet is one of the research directions for solving the above problems.

[0003] In view of this situation, it is necessary to provide an improved negative electrode active material, and an electrochemical device and an electronic device using the same.

Summary of the Invention

[0004] Embodiments of the present invention provide a negative electrode active material, and an electrochemical device and an electronic device using the same, thereby solving at least one problem in related fields to some extent.

[0005] According to one aspect of the present invention, a negative electrode active material is provided, the negative electrode active material contains a carbon material, where the carbon material satisfies the following relationship: 6 < Gr / K < 16, where Gr is the graphitization degree of the carbon material obtained by measurement by X-ray diffraction method, and K is the 1250 cm of the carbon material obtained by measurement by Raman spectroscopy.-1 ~1650 cm -1 The peak intensity Id at ~1650 cm of the carbon material and the peak intensity Ig at 1500 cm of the carbon material, i.e., Id / Ig, and K is 0.06 to 0.15. -1 ~1650 cm -1 The ratio of the peak intensity Ig at ~1650 cm, i.e., Id / Ig, and K is 0.06 to 0.15.

[0006] In some embodiments, the carbon material satisfies the relational expression 8 < Gr / K < 15. In some embodiments, the carbon material satisfies the relational expression 10 < Gr / K < 12. In some embodiments, the Gr / K value of the carbon material is 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5, or within the range composed of any two of the above values.

[0007] In some embodiments, K of the carbon material is 0.08 to 0.10. In some embodiments, K of the carbon material is 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or within the range composed of any two of the above values.

[0008] According to an embodiment of the present invention, the graphitization degree Gr of the carbon material is 0.92 to 0.96. In some embodiments, the graphitization degree Gr of the carbon material is 0.92, 0.93, 0.94, 0.95, 0.96, or within the range composed of any two of the above values.

[0009] According to an embodiment of the present invention, the carbon material satisfies at least one of the following relationships. Lc / S < 9, La / S > 20, Here, La is the crystallite size along the horizontal axis of the carbon material crystal measured by X-ray diffraction method, and the unit is nm. Lc is the crystallite size along the vertical axis of the carbon material crystal measured by X-ray diffraction method, and the unit is nm. S is the ratio of the peak area C004 of the (004) plane of the negative electrode active material obtained by measuring the X-ray diffraction pattern to the peak area C110 of the (110) plane, The Lc is less than 45 and the La is greater than 50.

[0010] In some embodiments, Lc / S<8. In some embodiments, Lc / S<7. In some embodiments, Lc / S<6. In some embodiments, Lc / S>2. In some embodiments, Lc / S>3. In some embodiments, Lc / S is 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, or within a range formed by any two of the aforementioned endpoints.

[0011] In some embodiments, La / S>22. In some embodiments, La / S>25. In some embodiments, La / S>28. In some embodiments, La / S>30. In some embodiments, La / S<60. In some embodiments, La / S<55. In some embodiments, La / S<50. In some embodiments, La / S is 22, 25, 28, 30, 35, 40, 45, 50, or within a range formed by any two of the aforementioned endpoints.

[0012] In some embodiments, the Lc is less than 40. In some embodiments, the Lc is less than 35. In some embodiments, the Lc is less than 30. In some embodiments, the Lc is less than 25. In some embodiments, the Lc is greater than 10. In some embodiments, the Lc is greater than 15. In some embodiments, the Lc is greater than 20. In some embodiments, the Lc is 20, 22, 25, 28, 30, 35, 40, 43, or within a range consisting of any two of the foregoing values.

[0013] In some embodiments, the La is greater than 60. In some embodiments, the La is greater than 80. In some embodiments, the La is greater than 100. In some embodiments, the La is greater than 110. In some embodiments, the La is greater than 120. In some embodiments, the La is greater than 130. In some embodiments, the La is greater than 150. In some embodiments, the La is greater than 180. In some embodiments, the La is greater than 200. In some embodiments, the La is greater than 220. In some embodiments, the La is less than 300. In some embodiments, the La is less than 250. In some embodiments, the La is 55, 60, 70, 80, 90, 100, 120, 150, 180, 200, 230, 250, or within a range consisting of any two of the above values.

[0014] According to an embodiment of the present invention, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>23.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>25.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>28.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>30.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<50.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<45.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<40.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<35.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material, Dv90 / Dv10+Dv90, is 24, 26, 28, 30, 33, 35, or is within a range formed by any two of the above values. In the above relationship, the units of Dv90 and Dv10 are μm.

[0015] According to another aspect of the present invention, there is provided an electrochemical device comprising a positive electrode, an electrolyte, and a negative electrode, the negative electrode comprising a negative electrode active material layer and a current collector, the negative electrode active material layer comprising the negative electrode active material described in the present invention.

[0016] According to an embodiment of the present invention, the surface density of the negative electrode active material layer is 0.077 mg / mm 2 ~0.121mg / mm 2 The negative electrode active material layer has a compacted density of 1.70 g / cm 3 ~1.92g / cm 3 It is.

[0017] In some embodiments, the areal density of the negative electrode active material layer is 0.080 mg / mm 2 ~0.120mg / mm 2 In some embodiments, the surface density of the negative electrode active material layer is 0.085 mg / mm 2 ~0.110mg / mm 2 In some embodiments, the surface density of the negative electrode active material layer is 0.090 mg / mm 2 ~0.100mg / mm 2 In some embodiments, the surface density of the negative electrode active material layer is 0.077 mg / mm 2 , 0.080mg / mm 2 , 0.085 mg / mm 2 , 0.090mg / mm 2 , 0.095 mg / mm 2 , 0.100mg / mm 2 , 0.105mg / mm 2 , 0.110mg / mm 2 , 0.115mg / mm 2 , 0.120mg / mm 2 , 0.121 mg / mm 2 or in a range consisting of any two of the above values.

[0018] In some embodiments, the negative electrode active material layer has a compressed density of 1.75 g / cm 3 ~1.90g / cm 3 In some embodiments, the negative electrode active material layer has a compressed density of 1.80 g / cm 3 ~1.85g / cm 3 In some embodiments, the negative electrode active material layer has a compressed density of 1.70 g / cm 3 , 1.75g / cm 3 , 1.78g / cm 3 , 1.80g / cm 3 , 1.85g / cm 3 , 1.85g / cm 3 , 1.88g / cm 3 , 1.90g / cm 3 , 1.92g / cm 3 or in a range consisting of any two of the above values.

[0019] According to an embodiment of the present invention, the ratio S' of the peak area C004' of the (004) plane of the negative electrode active material layer measured by X-ray diffraction pattern in a fully discharged state to the peak area C110' of the (110) plane of the negative electrode active material layer is in the range of 10 to 20. In some embodiments, the ratio S' of the negative electrode active material layer measured by X-ray diffraction pattern in a fully discharged state is in the range of 12 to 18. In some embodiments, the ratio S' of the negative electrode active material layer measured by X-ray diffraction pattern in a fully discharged state is in the range of 14 to 16. In some embodiments, the ratio S' of the negative electrode active material layer measured by X-ray diffraction pattern in a fully discharged state is 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or in a range consisting of any two of the above values.

[0020] According to an embodiment of the present invention, the peel strength between the negative electrode active material layer and the negative electrode current collector is 6 N / m to 15 N / m. In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is 8 N / m to 14 N / m. In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is 10 N / m to 12 N / m. In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is 6 N / m, 7 N / m, 8 N / m, 9 N / m, 10 N / m, 11 N / m, 12 N / m, 13 N / m, 14 N / m, 15 N / m, or within a range formed by any two of the above values.

[0021] According to some embodiments of the present invention, the negative active material layer has a porosity of 20% to 40%. In some embodiments, the negative active material layer has a porosity of 25% to 35%. In some embodiments, the negative active material layer has a porosity of 28% to 32%. In some embodiments, the porosity of the negative active material layer is 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, or within a range formed by any two of the above values.

[0022] According to some embodiments of the present invention, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is 280° C. or higher. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is 300° C. or higher. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is 320° C. or higher. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is 340° C. or higher.

[0023] According to some embodiments of the present invention, when the electrochemical device is fully discharged, the thermal decomposition temperature of the negative electrode active material layer is 130° C. or higher. In some embodiments, when the electrochemical device is fully discharged, the thermal decomposition temperature of the negative electrode active material layer is 140° C. or higher. In some embodiments, when the electrochemical device is fully discharged, the thermal decomposition temperature of the negative electrode active material layer is 150° C. or higher. In some embodiments, when the electrochemical device is fully discharged, the thermal decomposition temperature of the negative electrode active material layer is 160° C. or higher.

[0024] According to a further aspect of the present invention, there is provided an electronic device comprising an electrochemical device as described herein.

[0025] Other aspects and advantages of the invention are set forth in part in the description that follows, are illustrated in part, or may be learned through the practice of embodiments of the invention. [Brief description of the drawings]

[0026] In the following, in order to explain the embodiments of the present invention, the drawings necessary for explaining the embodiments of the present invention or the prior art will be briefly described. It is obvious that the drawings described below are only a part of the embodiments of the present invention. Those skilled in the art can still obtain drawings of other embodiments according to the structures illustrated in these drawings without making creative efforts. [Figure 1] FIG. 1 shows a scanning electron microscope (SEM) image of the negative electrode active material used in Comparative Example 2, magnified 500 times. [Diagram 2] FIG. 2 shows a scanning electron microscope (SEM) image of the negative electrode active material used in Example 5, magnified 500 times. [Diagram 3] FIG. 3 shows a photograph of the appearance of the negative electrode active material used in Example 5 after cycling, in which there is no lithium deposition phenomenon. [Figure 4] FIG. 4 shows a photograph of the appearance of the negative electrode active material used in Comparative Example 1 after cycling, and the photograph shows the lithium deposition phenomenon. [Diagram 5] FIG. 5 shows a photograph of the appearance of the negative electrode active material used in Comparative Example 2 after cycling, which shows the severe lithium precipitation phenomenon. [Figure 6] FIG. 6 shows curves illustrating the relationship between the number of cycles at 25° C. and the cycle capacity retention rate of the lithium ion batteries in Comparative Example 1, Comparative Example 2, and Example 5. [Figure 7] FIG. 7 shows curves illustrating the relationship between the number of cycles at 45° C. and the cycle capacity retention rate of the lithium ion batteries in Comparative Example 1, Comparative Example 2, and Example 5. [Figure 8] FIG. 8 shows curves illustrating the relationship between the number of cycles at 25° C. and the cycle expansion rate of the lithium ion batteries in Comparative Example 1, Comparative Example 2, and Example 5. [Figure 9] FIG. 9 shows curves illustrating the relationship between the number of cycles at 45° C. and the cycle expansion rate of the lithium ion batteries in Comparative Example 1, Comparative Example 2, and Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Hereinafter, the embodiments of the present invention will be described in detail. In the specification of the present invention, the same or similar parts and parts having the same or similar functions are indicated by similar symbols. The embodiments described in the present invention and related drawings are exemplary and schematic, and are used to generally understand the present invention. The embodiments of the present invention should not be construed as limiting the present invention.

[0028] In the specific embodiments and claims, a list of terms connected by the term "at least one" means any combination of the listed terms. For example, if terms A and B are listed, "at least one of A and B" means only A, only B, or A and B. In other examples, if terms A, B, and C are listed, "at least one of A, B, and C" means only A, or only B, only C, A and B (excluding C), A and C (excluding B), B and C (excluding A), or any of A, B, C. Term A may include a single element or a plurality of elements. Term B may include a single element or a plurality of elements. Term C may include a single element or a plurality of elements.

[0029] With the widespread use of electrochemical devices (e.g., lithium-ion batteries), improvement of their performance is first and foremost required. Energy density, cycle characteristics, and rate characteristics are important indicators for evaluating the performance of lithium-ion batteries. So far, no effective means have been developed to simultaneously improve the energy density, cycle characteristics, and rate characteristics of lithium-ion batteries.

[0030] The present invention solves the above problems by optimizing the anode active material. Specifically, the present invention provides an anode active material, the anode active material includes a carbon material, where the carbon material satisfies the following relationship: 6 < Gr / K < 16, where Gr is the graphitization degree of the carbon material obtained by measurement by X-ray diffraction method, and K is the ratio of the peak intensity Id at 1250 cm -1 ~1650 cm -1 of the carbon material measured by Raman spectroscopy and the peak intensity Ig at 1500 cm -1 ~1650 cm -1 of the carbon material, that is, Id / Ig, and the K is 0.06 to 0.15.

[0031] In some embodiments, the graphitization degree Gr and K of the carbon material satisfy the following relationship: 8 < Gr / K < 15. In some embodiments, the graphitization degree Gr and K of the carbon material satisfy the following relationship: 10 < Gr / K < 12. In some embodiments, the ratio Gr / K of the graphitization degree Gr and K of the carbon material is 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5, or within the range composed of any two of the above values.

[0032] In some embodiments, K of the carbon material is 0.08 to 0.10. In some embodiments, K of the carbon material is 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or within the range composed of any two of the above values.

[0033] K of the carbon material can indicate the ratio of the surface defects and crystal regions of the material. K is measured by Raman spectroscopy. Specifically, using a light source of 523 nm (light shielding intensity 5%), 100 points are sampled in a region of 100 μm × 100 μm, and for the carbon material at 1250 cm -1 ~1650 cm -1 the peak intensity Id and the ratio of the peak intensity Ig of the carbon material at 1500 cm -1 ~1650 cm -1 are calculated, and the average value is obtained as the K value of the carbon material.

[0034] The "graphitization degree" of the carbon material refers to the degree to which non-graphitic carbon is converted into graphitic carbon in the carbon material at high temperature or during secondary heating. The graphitization degree of the carbon material is obtained by the following method. Specifically, using high-purity silicon powder as an internal standard substance, the interplanar spacing (d002) of the 002 plane of the carbon material is measured by X-ray diffraction, and the graphitization degree Gr of the carbon material is calculated according to the following formula: Gr = (0.344 - d002) / 0.086 × 100%.

[0035] The graphitization degree and K value of the carbon material in the negative electrode active material affect the insertion and desorption of lithium ions. For example, during the discharge cycle of a lithium-ion battery, lithium ions move to the negative electrode, and the negative electrode accepts the lithium ions. The graphitization degree and K value of the carbon material affect the speed at which lithium ions are inserted into the carbon material particles. Under high-rate discharge conditions, if lithium ions cannot be inserted and diffused into the carbon material particles quickly, the lithium ions will precipitate on the surface, accelerating the cycle decay of the lithium-ion battery. During the charge cycle of a lithium-ion battery, lithium ions are desorbed from the negative electrode. If lithium ions cannot be desorbed from the negative electrode quickly, dead lithium will be formed inside the carbon material particles, which will also accelerate the cycle decay of the lithium-ion battery. The graphitization degree and K value of the carbon material also affect the thickness of the solid electrolyte interface (SEI) film formed during the first cycle of the lithium-ion battery, thereby affecting the first coulombic efficiency of the lithium-ion battery, and thus the energy density of the lithium-ion battery.

[0036] When the carbon material has a relatively high degree of graphitization (e.g., Gr>0.96), the crystal plane spacing of the carbon material becomes narrow, which is unfavorable for the desorption of lithium ions from the carbon material. When the carbon material has a relatively low degree of graphitization (e.g., Gr<0.92), the SPs in the carbon material 3 The relatively large number of bonds binds the layers of the carbon material together, making the structure of the carbon material more stable.

[0037] When the graphitization degree Gr of the carbon material and the ratio Gr / K of the graphitization degree to K of the carbon material are within the above ranges, the lithium ion battery has significantly improved energy density, cycle characteristics, and rate characteristics.

[0038] According to an embodiment of the present invention, the graphitization degree Gr of the carbon material is 0.92 to 0.96. In some embodiments, the graphitization degree Gr of the carbon material is 0.92, 0.93, 0.94, 0.95, 0.96, or within a range formed by any two of the above values. When the graphitization degree of the carbon material is within the above range, it contributes to further improving the energy density, cycle characteristics, and rate characteristics of the lithium ion battery.

[0039] According to an embodiment of the present invention, the carbon material satisfies at least one of the following relationships: Lc / S<9, La / S>20, Where: La is the crystallite size along the horizontal axis of the carbon material crystal measured by X-ray diffraction, and is expressed in nm; Lc is the crystallite size along the vertical axis of the carbon material crystal as measured by X-ray diffraction, in nm; S is the ratio of the peak area C004 of the (004) plane of the negative electrode active material obtained by measuring the X-ray diffraction pattern to the peak area C110 of the (110) plane, The Lc is less than 45 and the La is greater than 50.

[0040] In some embodiments, Lc / S<8. In some embodiments, Lc / S<7. In some embodiments, Lc / S<6. In some embodiments, Lc / S>2. In some embodiments, Lc / S>3. In some embodiments, Lc / S is 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, or within a range formed by any two of the aforementioned endpoints.

[0041] In some embodiments, La / S>22. In some embodiments, La / S>25. In some embodiments, La / S>28. In some embodiments, La / S>30. In some embodiments, La / S<60. In some embodiments, La / S<55. In some embodiments, La / S<50. In some embodiments, La / S is 22, 25, 28, 30, 35, 40, 45, 50, or within a range formed by any two of the aforementioned endpoints.

[0042] In some embodiments, the Lc is less than 40. In some embodiments, the Lc is less than 35. In some embodiments, the Lc is less than 30. In some embodiments, the Lc is less than 25. In some embodiments, the Lc is greater than 10. In some embodiments, the Lc is greater than 15. In some embodiments, the Lc is greater than 20. In some embodiments, the Lc is 20, 22, 25, 28, 30, 35, 40, 43, or within a range consisting of any two of the foregoing values.

[0043] In some embodiments, the La is greater than 60. In some embodiments, the La is greater than 80. In some embodiments, the La is greater than 100. In some embodiments, the La is greater than 110. In some embodiments, the La is greater than 120. In some embodiments, the La is greater than 130. In some embodiments, the La is greater than 150. In some embodiments, the La is greater than 180. In some embodiments, the La is greater than 200. In some embodiments, the La is greater than 220. In some embodiments, the La is less than 300. In some embodiments, the La is less than 250. In some embodiments, the La is 55, 60, 70, 80, 90, 100, 120, 150, 180, 200, 230, 250, or within a range consisting of any two of the above values.

[0044] The crystallite size of the carbon material crystals affects the insertion and desorption of lithium ions during cycling. The ratio S of the peak area C004 of the (004) plane of the negative electrode active material obtained from the X-ray diffraction pattern to the peak area C110 of the (110) plane of the negative electrode active material can indicate the degree of orientation of the negative electrode active material. The larger S is, the greater the anisotropy of the negative electrode active material. The smaller S is, the greater the isotropy of the negative electrode active material. If the crystallite size of the carbon material and the ratio of the crystallite size to the degree of orientation are within the above ranges, this contributes to further improving the energy density, cycle characteristics, and rate characteristics of the lithium ion battery.

[0045] According to an embodiment of the present invention, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>23.0, and the units of Dv90 and Dv10 are μm. "Dv90" refers to a particle size at which the cumulative volume from the small particle size side is 90% in the particle size distribution on a volume basis of the negative electrode active material, that is, the volume of the negative electrode active material smaller than the particle size occupies 90% of the total volume of the negative electrode active material. "Dv10" refers to a particle size at which the cumulative volume from the small particle size side is 10% in the particle size distribution on a volume basis of the negative electrode active material, that is, the volume of the negative electrode active material smaller than the particle size occupies 10% of the total volume of the negative electrode active material. The particle size of the negative electrode active material is obtained by measuring with a particle size measuring device (e.g., Malvern particle size distribution measuring device).

[0046] In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>25.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>28.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>30.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<50.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<45.0. In some embodiments, the negative active material has a Dv10 value and a Dv90 value that satisfy the following relationship: Dv90 / Dv10+Dv90<40.0. In some embodiments, the negative active material has a Dv10 value and a Dv90 value that satisfy the following relationship: Dv90 / Dv10+Dv90<35.0. In some embodiments, the negative active material has a Dv90 / Dv10+Dv90 value that is 24, 26, 28, 30, 33, 35, or within a range formed by any two of the above values. In the above relationships, the units of Dv90 and Dv10 are μm.

[0047] When the particle size of the negative electrode active material is relatively large, the specific surface area of ​​the negative electrode active material is relatively small, so that the lithium ion battery needs to consume relatively few lithium ions to form a solid electrolyte interface (SEI) film with the electrolyte during the first cycle, thereby improving the initial coulombic efficiency of the lithium ion battery. In addition, the relatively large particle size can extend the path of lithium ion insertion and desorption, thereby degrading the dynamic properties of the lithium ion battery. In addition, the relatively large particle size also has a negative effect on the post-cycle expansion of the lithium ion battery. Conversely, when the particle size of the negative electrode active material is relatively small, the specific surface area of ​​the negative electrode active material is relatively large, so that the lithium ion battery needs to consume more lithium ions to form a SEI film with the electrolyte during the first cycle, thereby reducing the initial coulombic efficiency of the lithium ion battery. In addition, the relatively small particle size can shorten the path of lithium ion insertion and desorption, thereby affecting the dynamic properties of the lithium ion battery. In addition, the relatively small particle size also has a negative effect on the post-cycle expansion of the lithium ion battery. When the Dv90 and Dv10 of the negative electrode active material satisfy the above-mentioned relationship, the various characteristics of the ion battery are balanced, which contributes to further improving the energy density, cycle characteristics, and rate characteristics of the lithium ion battery.

[0048] The present invention also provides an electrochemical device including a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode, the negative electrode, the separator, and the electrolyte used in the present invention will be described below.

[0049] negative electrode The negative electrode used in the electrochemical device of the present invention includes a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer includes the negative electrode active material described in the present invention.

[0050] According to an embodiment of the present invention, the surface density of the negative electrode active material layer is 0.077 mg / mm 2 ~0.121mg / mm 2 and the compressed density of the negative electrode active material layer is 1.70 g / cm 3 ~1.92g / cm3 It is.

[0051] In some embodiments, the areal density of the negative electrode active material layer is 0.080 mg / mm 2 ~0.120mg / mm 2 In some embodiments, the surface density of the negative electrode active material layer is 0.085 mg / mm 2 ~0.110mg / mm 2 In some embodiments, the surface density of the negative electrode active material layer is 0.090 mg / mm 2 ~0.100mg / mm 2 In some embodiments, the surface density of the negative electrode active material layer is 0.077 mg / mm 2 , 0.080mg / mm 2 , 0.085 mg / mm 2 , 0.090mg / mm 2 , 0.095 mg / mm 2 , 0.100mg / mm 2 , 0.105mg / mm 2 , 0.110mg / mm 2 , 0.115mg / mm 2 , 0.120mg / mm 2 , 0.121 mg / mm 2 or within a range consisting of any two of the above values. The surface density of the negative electrode active material layer is measured and obtained by the following method. Specifically, the battery is discharged to 0 SOC%, the battery is disassembled, washed, and dried, and the negative electrode (both sides of the negative electrode current collector are coated with the negative electrode active material layer) having a certain area A is weighed using an electronic balance, and the weight is W1. The negative electrode active material layer is washed off using a solvent, dried, and the weight of the negative electrode current collector is measured, and the weight is W2. The surface density of the negative electrode active material layer is calculated by the following formula: (W1-W2) / (A×2).

[0052] In some embodiments, the negative electrode active material layer has a compressed density of 1.75 g / cm 3 ~1.90g / cm 3 In some embodiments, the negative electrode active material layer has a compressed density of 1.80 g / cm 3 ~1.85g / cm 3In some embodiments, the negative electrode active material layer has a compressed density of 1.70 g / cm 3 , 1.75g / cm 3 , 1.78g / cm 3 , 1.80g / cm 3 , 1.85g / cm 3 , 1.85g / cm 3 , 1.88g / cm 3 , 1.90g / cm 3 , 1.92g / cm 3 or in a range formed by any two of the above values. The compression density of the negative electrode active material layer is measured and obtained by the following method. Specifically, the battery is discharged to 0 SOC%, disassembled, washed, and dried, and the negative electrode (the negative electrode active material layer is applied to both sides of the negative electrode current collector) having a certain area A is weighed using an electronic balance, and the weight is W1. The thickness T1 of the negative electrode is measured using a ten-thousandth micrometer. The negative electrode active material layer is washed off using a solvent, dried, and the weight of the negative electrode current collector is measured, and the weight is W2. The thickness T2 of the negative electrode current collector is measured using a ten-thousandth micrometer. The weight W0 and thickness T0 of the negative electrode active material layer disposed on one side of the negative electrode current collector, and the compression density of the negative electrode active material layer are calculated according to the following formula: W0 = (W1 - W2) / 2 T0=(T1-T2) / 2 Compressed density = W0 / (T0 x A).

[0053] According to an embodiment of the present invention, the ratio S' of the peak area C004' of the (004) plane of the negative electrode active material layer measured by X-ray diffraction pattern in a fully discharged state to the peak area C110' of the (110) plane of the negative electrode active material layer is in the range of 10 to 20. In some embodiments, the ratio S' of the negative electrode active material layer measured by X-ray diffraction pattern in a fully discharged state is in the range of 12 to 18. In some embodiments, the ratio S' of the negative electrode active material layer measured by X-ray diffraction pattern in a fully discharged state is in the range of 14 to 16. In some embodiments, the ratio S' of the negative electrode active material layer measured by X-ray diffraction pattern in a fully discharged state is 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or in the range consisting of any two of the above values. S' may indicate the degree of orientation of the negative electrode active material layer. The larger S' is, the greater the anisotropy of the negative electrode active material layer is. The smaller S' is, the greater the isotropy of the negative electrode active material layer.

[0054] According to an embodiment of the present invention, the peel strength between the negative electrode active material layer and the negative electrode current collector is 6 N / m to 15 N / m. In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is 8 N / m to 14 N / m. In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is 10 N / m to 12 N / m. In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is 6 N / m, 7 N / m, 8 N / m, 9 N / m, 10 N / m, 11 N / m, 12 N / m, 13 N / m, 14 N / m, 15 N / m, or within a range formed by any two of the above values.

[0055] The peel strength between the negative electrode active material layer and the negative electrode current collector is obtained by a tensile test. Specifically, an Instron (33652 type) measuring device is used to measure the adhesion between the negative electrode active material layer and the negative electrode current collector. More specifically, a 15-20 mm long electrode sheet is taken, fixed to a steel plate with 3M double-sided tape, the tape is attached to the surface of the negative electrode active material layer, one side of the tape is connected to a paper tape of equal width, the limit block of the tension machine is adjusted to an appropriate position, the paper tape is folded upward, and slid 40 mm, the sliding speed is 50 mm / min, and the peel strength between the negative electrode active material layer and the negative electrode current collector at 180° (i.e., stretched in the opposite direction) is measured.

[0056] According to an embodiment of the present invention, the negative active material layer has a porosity of 20% to 40%. In some embodiments, the negative active material layer has a porosity of 25% to 35%. In some embodiments, the negative active material layer has a porosity of 28% to 32%. In some embodiments, the porosity of the negative active material layer is 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, or within a range consisting of any two of the above values. The porosity of the negative active material layer is obtained by the standard test of "GB / T24586-2009 Measurement of Surface Density, True Density and Porosity of Iron Ore".

[0057] When the surface density of the negative electrode active material layer is constant, decreasing the compressed density of the negative electrode active material layer reduces the anisotropy and porosity of the negative electrode active material layer, and reduces the peel strength between the negative electrode active material layer and the negative electrode current collector. When the compressed density of the negative electrode active material layer is constant, decreasing the surface density of the negative electrode active material layer increases the anisotropy of the negative electrode active material layer, reduces the porosity of the negative electrode active material layer, and reduces the peel strength between the negative electrode active material layer and the negative electrode current collector. When the surface density, compressed density, degree of orientation S', porosity, and / or peel strength between the negative electrode active material layer and the negative electrode current collector are within the above ranges, this contributes to further improving the energy density, cycle characteristics, and rate characteristics of the lithium ion battery.

[0058] According to an embodiment of the present invention, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is 280° C. or higher. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is 300° C. or higher. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is 320° C. or higher. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is 340° C. or higher. When the electrochemical device is fully charged, lithium ions are inserted into the pores of the negative electrode material, and the thermal decomposition temperature of the negative electrode active material layer can represent the degree of high-temperature aging of the negative electrode, i.e., the higher the decomposition temperature of the negative electrode active material, the lower the degree of high-temperature aging, and the better the high-temperature cycle characteristics of the lithium ion battery.

[0059] According to an embodiment of the present invention, when the electrochemical device is fully discharged, the thermal decomposition temperature of the negative electrode active material layer is 130° C. or higher. In some embodiments, when the electrochemical device is fully discharged, the thermal decomposition temperature of the negative electrode active material layer is 140° C. or higher. In some embodiments, when the electrochemical device is fully discharged, the thermal decomposition temperature of the negative electrode active material layer is 150° C. or higher. In some embodiments, when the electrochemical device is fully discharged, the thermal decomposition temperature of the negative electrode active material layer is 160° C. or higher. When the electrochemical device is fully discharged, all lithium ions are desorbed from the negative electrode, and the thermal decomposition temperature of the negative electrode active material layer can indirectly indicate the stability of the SEI film, i.e., the higher the thermal decomposition temperature of the negative electrode active material layer, the better the thermal stability of the SEI film, and the fewer lithium ions consumed to repair the SEI film during the cycle of the lithium ion battery, resulting in better cycle characteristics of the lithium ion battery.

[0060] The thermal decomposition temperature of the negative electrode active material layer can be measured by differential scanning calorimetry (DSC). Specifically, a differential scanning calorimeter is used to heat a negative electrode active material layer for measurement at a fixed heating rate from 0 to 800° C. to measure the thermal decomposition temperature.

[0061] The negative electrode current collector used in the present invention may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, conductive metal coated polymer substrate, and combinations thereof.

[0062] According to an embodiment of the present invention, the negative electrode further comprises a conductive layer. In some embodiments, the conductive material of the conductive layer may comprise any conductive material as long as it does not cause chemical changes. Non-limiting examples of the conductive material include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanotube, graphene, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., e.g., copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof.

[0063] According to an embodiment of the present invention, the negative electrode further includes a binder, and the binder is at least one selected from the group consisting of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, poly(1,1-difluoroethylene), polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon.

[0064] positive electrode The positive electrode includes a positive electrode current collector and a positive electrode active material disposed on the positive electrode current collector. The specific type of the positive electrode active material is not particularly limited and may be selected as necessary.

[0065] In some embodiments, the positive electrode active material includes a positive electrode material capable of absorbing and releasing lithium (Li). Examples of positive electrode materials capable of absorbing and releasing lithium (Li) may include lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminate, lithium manganese oxide, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxide phosphate, lithium iron phosphate, lithium titanate, and lithium-rich manganese-based materials.

[0066] Specifically, the chemical formula of lithium cobalt oxide may be represented by Chemical Formula 1. (chemical 1) Li x Co a M1 b O 2-c chemical formula 1 Here, M1 represents at least one selected from the group consisting of nickel (Ni), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), yttrium (Y), lanthanum (La), zirconium (Zr), and silicon (Si), and the values ​​of x, a, b, and c are within the ranges of 0.8≦x≦1.2, 0.8≦a≦1, 0≦b≦0.2, and −0.1≦c≦0.2, respectively.

[0067] The chemical formula of lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminate may be represented by Chemical Formula 2. (Case 2) Li y Ni d M2 e O 2-f chemical formula 2 Here, M2 represents at least one selected from the group consisting of cobalt (Co), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), zirconium (Zr), and silicon (Si), and the values ​​of y, d, e, and f are within the ranges of 0.8≦y≦1.2, 0.3≦d≦0.98, 0.02≦e≦0.7, and −0.1≦f≦0.2, respectively.

[0068] The chemical formula of lithium manganate may be represented by Chemical Formula 3. (3) Li z Mn 2-g M3 g O 4-h chemical formula 3 Here, M3 represents at least one selected from the group consisting of cobalt (Co), nickel (Ni), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), and tungsten (W), and the values ​​of z, g, and h are within the ranges of 0.8≦z≦1.2, 0≦g<1.0, and −0.2≦h≦0.2, respectively.

[0069] In some embodiments, the weight of the positive electrode active material layer is 1.5 to 15 times the weight of the negative electrode active material layer. In some embodiments, the weight of the positive electrode active material layer is 3 to 10 times the weight of the negative electrode active material layer. In some embodiments, the weight of the positive electrode active material layer is 5 to 8 times the weight of the negative electrode active material layer. In some embodiments, the weight of the positive electrode active material layer is 1.5 times, 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, 11 times, 12 times, 13 times, 14 times, or 15 times the weight of the negative electrode active material layer.

[0070] In some embodiments, the positive electrode active material layer may have a coating on the surface or may be mixed with another compound having a coating. The coating may include at least one compound of the applied element selected from the group consisting of an oxide of the applied element, a hydroxide of the applied element, an oxyhydroxide of the applied element, an oxycarbonate of the applied element, and a hydroxycarbonate of the applied element. The compound used in the coating may be amorphous or crystalline. The applied element contained in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, F, and mixtures thereof. The coating may be formed by any method as long as it does not adversely affect the performance of the positive electrode active material. For example, the method may include any application method known to those skilled in the art, such as spraying, dipping, etc.

[0071] In some embodiments, the positive electrode active material layer further comprises an adhesive, and optionally further comprises a positive electrode conductive material.

[0072] The adhesive can enhance the bonding between the positive electrode active material particles and the positive electrode active material and the current collector. Non-limiting examples of the adhesive include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, poly(1,1-difluoroethylene), polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, etc.

[0073] The positive electrode active material layer contains a positive electrode conductive material, thereby imparting electrical conductivity to the electrode. The positive electrode conductive material may contain any conductive material as long as it does not cause a chemical change. Non-limiting examples of the positive electrode conductive material include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof.

[0074] The positive electrode current collector used in the electrochemical device according to the present invention may be, but is not limited to, aluminum (Al).

[0075] electrolyte The electrolyte used in the embodiments of the present invention may be any electrolyte known in the prior art. The electrolyte used in the electrolyte solution of the embodiment of the present invention is, for example, an inorganic lithium salt such as LiClO4, LiAsF6, LiPF6, LiBF4, LiSbF6, LiSO3F, LiN(FSO2)2, for example, LiCF3SO3, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,3-hexafluoropropane disulfonimide lithium, cyclic 1,2-tetrafluoroethane disulfonimide lithium, LiN(CF3SO2)(C4F9SO2), LiC(CF3SO2)3, LiPF4(CF3)2, LiPF 4(C2F5)2, LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2, fluorine-containing organic lithium salts, such as dicarboxylic acid complex lithium salts such as lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate, but are not limited thereto. Note that the above electrolytes may be used alone or in combination of two or more. In some embodiments, the electrolyte includes a combination of LiPF6 and LiBF4. In some embodiments, the electrolyte includes a combination of an inorganic lithium salt, such as LiPF6 or LiBF4, and a fluorine-containing organic lithium salt, such as LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, etc. In some embodiments, the electrolyte includes LiPF6.

[0076] In some embodiments, the concentration of the electrolyte is in the range of 0.8 mol / L to 3 mol / L, such as in the range of 0.8 mol / L to 2.5 mol / L, such as in the range of 0.8 mol / L to 2 mol / L, such as in the range of 1 mol / L to 2 mol / L, such as 1 mol / L, 1.15 mol / L, 1.2 mol / L, 1.5 mol / L, 2 mol / L, or 2.5 mol / L.

[0077] Solvents used in the electrolyte of the embodiment of the present invention include, but are not limited to, cyclic carbonates, chain carbonates, cyclic carboxylic acid esters, chain carboxylic acid esters, cyclic ethers, or chain ethers.

[0078] In some embodiments, cyclic carbonates include, but are not limited to, ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate.

[0079] In some embodiments, the cyclic carbonate has 3 to 6 carbon atoms.

[0080] In some embodiments, the chain carbonate includes, but is not limited to, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate (DEC), methyl-n-propyl carbonate, ethyl-n-propyl carbonate, di-n-propyl carbonate, and the like; and the chain carbonate substituted with fluorine includes, for example, bis(fluoromethyl)carbonate, bis(difluoromethyl)carbonate, bis(trifluoromethyl)carbonate, bis(2-fluoroethyl)carbonate, bis(2,2-difluoroethyl)carbonate, bis(2,2,2-trifluoroethyl)carbonate, 2-fluoroethylmethylcarbonate, 2,2-difluoroethylmethylcarbonate, and 2,2,2-trifluoroethylmethylcarbonate.

[0081] In some embodiments, the cyclic carboxylic acid ester includes, but is not limited to, γ-butyrolactone and γ-valerolactone. In some embodiments, a portion of the hydrogen of the cyclic carboxylic acid ester may be replaced with fluorine.

[0082] In some embodiments, the chain carboxylic acid ester includes, but is not limited to, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate, t-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate, ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate, and ethyl pivalate. In some embodiments, a part of the hydrogen of the chain carboxylic acid ester may be replaced with fluorine. In some embodiments, the chain carboxylic acid ester substituted with fluorine includes, but is not limited to, methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, butyl trifluoroacetate, and 2,2,2-trifluoroethyl trifluoroacetate.

[0083] In some embodiments, cyclic ethers include, but are not limited to, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl-1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, and dimethoxypropane.

[0084] In some embodiments, linear ethers include, but are not limited to, dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane, and 1,2-ethoxymethoxyethane.

[0085] In some embodiments, the solvent used in the electrolyte of the present invention includes one or more of the solvents described above. In some embodiments, the solvent used in the electrolyte of the present invention includes cyclic carbonates, linear carbonates, cyclic carboxylic acid esters, linear carboxylic acid esters, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present invention includes an organic solvent selected from the group consisting of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, n-propyl acetate, ethyl acetate, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present invention includes ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, gamma-butyrolactone, and combinations thereof.

[0086] Additives that may be used in the electrolyte of embodiments of the present invention include, but are not limited to, cyclic carbonates that contain carbon-carbon double bonds, and compounds that contain sulfur-oxygen double bonds.

[0087] In some embodiments, the cyclic carbonate containing a carbon-carbon double bond specifically includes, but is not limited to, at least one of vinylene carbonate, methylvinylene carbonate, ethylvinylene carbonate, vinylethylene carbonate, or 1,2-dimethylvinylene carbonate.

[0088] In some embodiments, the compound containing a sulfur-oxygen double bond includes, but is not limited to, at least one of ethylene sulfate, 1,2-propanediol sulfate, 1,3-propane sultone, 1-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, or 3-fluoro-1,3-propane sultone.

[0089] Separator In some embodiments, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the embodiments of the present invention are not particularly limited and may be any of those disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic material formed from a material that is stable against the electrolyte of the present invention.

[0090] For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a nonwoven fabric, a membrane, or a composite membrane having a porous structure, and the material of the substrate layer is at least one selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be selected and used. The porous structure improves the heat resistance, oxidation resistance, and electrolyte infiltration of the separator, and enhances the adhesion between the separator and the electrode sheet.

[0091] A surface treatment layer is provided on at least one surface of the base layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or may be a layer made of a mixture of a polymer and an inorganic material.

[0092] The inorganic layer includes inorganic particles and a binder, the inorganic particles being one or more combinations selected from the group consisting of alumina, silica, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium oxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate, and the binder being one or more combinations selected from the group consisting of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene.

[0093] The polymer layer includes a polymer, and the polymer material is at least one selected from the group consisting of polyamide, polyacrylonitrile, polymer of acrylic ester, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).

[0094] Electrochemical Equipment The present invention further provides an electrochemical device comprising a positive electrode, an electrolyte, and a negative electrode, the positive electrode comprising a positive electrode active material layer and a positive electrode current collector, the negative electrode comprising a negative electrode active material layer and a negative electrode current collector, and the negative electrode active material layer comprising the negative electrode active material described in the present invention.

[0095] The electrochemical device of the present invention includes any device in which an electrochemical reaction occurs, including, for example, any type of primary battery, secondary battery, fuel cell, solar cell, or capacitor, and in particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0096] electronic equipment The present invention further provides an electronic device comprising an electrochemical device according to the present invention.

[0097] The electrochemical device of the present invention can be used in any electronic device known in the prior art without any particular limitation.In some embodiments, the electrochemical device of the present invention can be used in, but is not limited to, notebook computers, pen-input computers, mobile computers, electronic book players, mobile phones, portable facsimiles, portable copy machines, portable printers, stereo headsets, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, automobiles, motorcycles, auxiliary bicycles, bicycles, lighting equipment, toys, game machines, clocks, power tools, flashlights, cameras, large household storage batteries, and lithium ion capacitors.

[0098] In the following, the preparation of a lithium ion battery is described with reference to specific examples, taking a lithium ion battery as an example, and those skilled in the art should understand that the preparation method described in the present invention is only illustrative, and any other suitable preparation method is within the scope of the present invention.

[0099] Working Example In the following, examples and comparative examples of the lithium ion battery according to the present invention will be described and performance evaluation will be performed.

[0100] 1. Preparation of lithium-ion batteries 1. Preparation of the negative electrode Artificial graphite was crushed, and the particle size distribution was controlled by sieving so that Dv90<25μm, to obtain primary particles. A binder was added to the primary particles to bind them, and the particle size distribution was controlled by sieving so that Dv90<45μm, to obtain secondary particles. The primary particles and secondary particles were graphitized at 2300-3500℃, and then the treated primary particles and secondary particles were mixed and sieved to obtain a graphite negative electrode material.

[0101] The graphite anode material prepared as described above, additives, binder styrene butadiene rubber (SBR) and thickener sodium carboxymethyl cellulose (CMC) were mixed in a weight ratio of 97:1.5:1.5, and mixed in an appropriate amount of deionized water with sufficient stirring to form a uniform anode slurry that did not settle. The anode slurry was applied onto an anode current collector (copper foil), dried and cold rolled to obtain an anode active material layer, which was then cut into pieces to obtain an anode.

[0102] The degree of graphitization and K of the graphite material in the negative electrode can be controlled by the raw material, particle size, graphitization temperature, and the compounding ratio of primary particles to secondary particles.

[0103] 2. Preparation of the positive electrode Lithium cobalt oxide (Li x Co a M1 b O 2-c, x, a, b and c values ​​are within the following ranges: 0.8≦x≦1.2, 0.8≦a≦1, 0≦b≦0.2, -0.1≦c≦0.2, M1 is manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), and combinations thereof), acetylene black, and vinylidene fluoride (PVDF) were mixed in a weight ratio of 95:2:3 with a suitable amount of N-methylpyrrolidone (NMP) as a solvent, and stirred thoroughly to form a uniform positive electrode slurry. The positive electrode slurry was applied onto an aluminum foil as a positive electrode current collector, dried, and cold-rolled to obtain a positive electrode active material layer, which was then cut into pieces to obtain a positive electrode.

[0104] 3. Preparation of electrolyte In a glove box filled with a dry argon gas atmosphere, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a weight ratio of 1:1:1. Next, 2% fluoroethylene carbonate, 2% 1,3-propane sultone, and 2% butanedinitrile were added and dissolved. After thorough stirring, the lithium salt LiPF6 was added and mixed uniformly, and an electrolyte with a LiPF6 concentration of 1 mol / L was obtained.

[0105] 4. Preparation of separator A polyethylene (PE) porous polymer film is used as the separator.

[0106] 5. Preparation of Lithium-ion Battery The positive electrode, separator, and negative electrode are stacked in this order so that the separator is interposed between the positive electrode and the negative electrode to play a role of isolation, and then wound to obtain a bare cell. After welding the tabs, the bare cell is placed in an aluminum packaging exterior, and the electrolyte prepared as described above is injected into the dried bare cell, which is then vacuum packaged, left to stand, formed, shaped, capacity measured, and other processes to obtain a lithium-ion battery.

[0107] 2.Measurement method 1. Measurement method of K value of carbon materials Using a 523 nm light source (light shielding strength 5%), 100 points were collected in an area of ​​100 μm × 100 μm, and the 1250 cm -1 ~1650cm -1 Peak intensity Id at 1500 cm of carbon material -1 ~1650cm -1 The ratio of the peak intensity Ig at each point is calculated, and the average value is calculated as the K value of the carbon material.

[0108] 2. Measurement method for the graphitization degree of carbon materials High-purity silicon powder (purity ≥ 99.99%) was used as an internal standard material, and the carbon material and silicon were mixed at a weight ratio of 5:1, uniformly polished, and pressed to prepare a sheet-shaped sample. The lattice spacing (d002) of the 002 plane of the carbon material was measured using an X-ray diffractometer (CuKα target), and the graphitization degree Gr of the carbon material was calculated according to the following formula. Gr=(0.344-d002) / 0.086×100%.

[0109] 3. Method for measuring the degree of orientation S of the negative electrode active material and the degree of orientation S' of the negative electrode active material layer According to the People's Republic of China Mechanical Industry Standard JB / T4220-2011 "Method for measuring lattice constant of artificial graphite", the (004) plane diffraction ray pattern and the (110) plane diffraction ray pattern in the X-ray diffraction pattern of the negative electrode active material and the negative electrode active material layer were measured. The test conditions are as follows. X-ray adopts CuKα radiation, and CuKα radiation is removed by a filter or monochromator. The operating voltage of the X-ray tube is 35-45kV, and the operating current is 30-50mA. The scanning speed of the counter is 0.3(°) / min. When recording the diffraction ray pattern of the (004) plane, the scanning range of the diffraction angle 2θ is 52°~58°. When recording the diffraction ray pattern of the (110) plane, the scanning range of the diffraction angle 2θ is 70°~79°.

[0110] The peak area of ​​the negative electrode active material obtained from the diffraction line pattern of the (004) plane is designated as C004. The peak area of ​​the negative electrode active material obtained from the diffraction line pattern of the (110) plane is designated as C110. The ratio of C004 / C110 of the negative electrode active material is calculated and designated as S.

[0111] The peak area of ​​the negative electrode active material layer obtained from the diffraction line pattern of the (004) plane is designated as C004'. The peak area of ​​the negative electrode active material layer obtained from the diffraction line pattern of the (110) plane is designated as C110'. The ratio of C004' / C110' of the negative electrode active material is calculated and designated as S'.

[0112] 4. Method for measuring the crystallite size of carbon materials The crystallite size La along the horizontal axis and the crystallite size Lc along the vertical axis of the carbon material in the negative electrode active material were analyzed and measured using an X-ray diffractometer.

[0113] 5. Method for measuring particle size of negative electrode active material A Malvern particle size analyzer was used to measure the particle size of the negative active material. Specifically, the negative active material was dispersed in ethanol, which is a dispersant, and ultrasonically treated for 30 minutes. The sample was then placed in the Malvern particle size analyzer to measure the Dv90 and Dv10 of the negative active material.

[0114] 6. Method for measuring the surface density of the negative electrode active material layer Discharge the battery to 0 SOC%, disassemble the battery, wash, dry, and weigh the negative electrode (negative electrode active material layer applied to both sides of the negative electrode current collector) having a certain area A using an electronic balance, and define the weight as W1. Wash off the negative electrode active material layer using a solvent, dry, and measure the weight of the negative electrode current collector, and define it as W2. Calculate the areal density of the negative electrode active material layer using the following formula: (W1-W2) / (A×2).

[0115] 7. Method for measuring the compressed density of the negative electrode active material layer The battery is discharged to 0 SOC%, disassembled, washed, and dried, and the negative electrode (negative electrode active material layer is applied to both sides of the negative electrode current collector) having a certain area A is weighed using an electronic balance, the weight is W1, and the thickness of the negative electrode is measured using a micrometer to the nearest ten thousandths. The negative electrode active material layer is washed off using a solvent, dried, the weight of the negative electrode current collector is measured, the weight is W2, and the thickness of the negative electrode current collector is measured using a micrometer to the nearest ten thousandths. The weight W0 and thickness T0 of the negative electrode active material layer disposed on one side of the negative electrode current collector, and the compression density of the negative electrode active material layer are calculated according to the following formulas. W0 = (W1 - W2) / 2 T0=(T1-T2) / 2 Compressed density = W0 / (T0 x A).

[0116] 8. Method for measuring peel strength between negative electrode active material layer and negative electrode current collector An Instron (model 33652) tension device is used to measure the adhesion between the negative active material layer and the negative current collector. Specifically, a 15-20 mm long electrode sheet is taken and fixed to a steel plate with 3M double-sided tape, the tape is attached to the surface of the negative active material layer, one side of the tape is connected to a paper tape of equal width, the limit block of the tension device is adjusted to an appropriate position, the paper tape is folded upward, and slid 40 mm at a sliding speed of 50 mm / min, and the peel strength between the negative active material layer and the negative current collector at 180° (i.e., stretched in the opposite direction) is measured.

[0117] 9. Method for measuring the porosity of the negative electrode active material layer The sample negative electrode active material layer was prepared into a complete wafer. For each example or comparative example, 30 samples were measured, and the volume of each sample was approximately 0.35 cm. 3 The porosity of the negative electrode active material layer is measured according to the standard "GB / T24586-2009 Iron Ore Surface Density, True Density and Porosity Measurement".

[0118] 10. Method for measuring the wetting time of the negative electrode active material layer 1 mL of the electrolyte is dropped onto the negative electrode active material layer, and timing is started. Timing is stopped until the electrolyte on the surface of the negative electrode active material layer is completely removed. In each example or comparative example, 100 data are measured, and the average value is calculated to determine the infiltration time of the negative electrode active material layer.

[0119] 11. Method for measuring the thermal decomposition temperature of the negative electrode active material layer A differential scanning calorimeter is used to measure the thermal decomposition temperature of the negative electrode active material layer decomposed in a fully charged or fully discharged state by heating at a fixed heating rate from 0 to 800°C.

[0120] 12. Measurement method for cycle capacity retention rate of lithium-ion batteries The lithium-ion battery is left at 45°C for 10 minutes, then charged at a constant current of 0.7C to 4.4V, discharged at a constant voltage of 4.4V to 0.05C, and left to stand for 10 minutes. Then, the battery is charged at a constant current of 0.7C to 3.0V, and left to stand for 10 minutes. This is considered as one cycle, and the discharge capacity of the first cycle is recorded. The above procedure is repeated 400 times, and the discharge capacity after the cycle is recorded. The cycle capacity retention rate of the lithium-ion battery is calculated using the following formula. Cycle capacity retention rate = (discharge capacity after cycling / discharge capacity of the first cycle) x 100%

[0121] Except that the working temperature is 25°C and the number of cycles is 800, the cycle capacity retention rate of the lithium ion battery at 25°C is measured according to the same procedure as above.

[0122] 13. Measurement method for cycle expansion rate of lithium-ion batteries The lithium-ion battery is left at 45°C for 10 minutes, then charged at a constant current of 0.7C to 4.4V, discharged at a constant voltage of 4.4V to 0.05C, and left to stand for 10 minutes. Then, it is charged at a constant current of 0.7C to 3.0V, and left to stand for 10 minutes. This is considered as one cycle, and the thickness of the lithium-ion battery at the first cycle is recorded. The above procedure is repeated 400 times, and the thickness of the lithium-ion battery after each cycle is recorded. The cycle expansion rate of the lithium-ion battery is calculated using the following formula: Cyclic expansion rate = (thickness after cycling / thickness of first cycle) x 100%

[0123] The cycle expansion rate of the lithium ion battery at 25°C is measured according to the same procedure as above, except that the operating temperature is 25°C and the cycle number is 800.

[0124] 14. Measurement method for lithium precipitation phenomenon in lithium-ion batteries At 25°C, the lithium-ion battery is discharged at a constant current of 0.5C to 3.0V, left to stand for 10 minutes, then charged at a constant current of 1.5C to 4.1V, charged at a constant voltage of 0.05C to 4.1V, charged at a constant current of 0.7C to 4.3V, charged at a constant voltage of 0.05C to 4.3V, charged at a constant current of 0.5C to 4.4V, charged at a constant voltage of 0.05C to 4.4V, and finally discharged at a constant current of 0.5C to 3.0V and left to stand for 10 minutes. The above charging and discharging operations are repeated 10 times. The lithium-ion battery is disassembled under dry conditions, photographed, and the state of the negative electrode is recorded.

[0125] The degree of lithium deposition in lithium-ion batteries is judged according to the following criteria. The disassembled negative electrode was golden yellow overall, and only a very small portion was observed to be gray, and the area of ​​the gray region was less than 2%. When this was the case, it was judged to have "no lithium deposition." When most of the decomposed negative electrode is golden yellow, gray is observed in some places, and the area of ​​the gray region is 2% to 20%, it is judged that "there is a small amount of lithium deposition." The decomposed negative electrode is entirely gray, golden yellow is observed in some parts, and the area of ​​the gray region is 20% to 60%. In this case, the negative electrode is judged to have "lithium deposition." When the entire decomposed negative electrode shows a gray color and the area of ​​the gray region exceeds 60%, it is judged that "lithium deposition is severe."

[0126] 3. Measurement results Table 1 shows the effect of the properties of the negative electrode active material on the performance of a lithium-ion battery.

[0127] As shown in Comparative Example 1, when the ratio Gr / K of the graphitization degree Gr to K of the negative electrode active material is less than 6 and K is greater than 0.15, the initial coulombic efficiency of the lithium ion battery is very low, lithium precipitation occurs (see FIG. 4), the cycle capacity retention rate is relatively low, and the cycle expansion rate is relatively high. As shown in Comparative Example 2, when the ratio Gr / K of the graphitization degree Gr to K of the negative electrode active material is greater than 16 and K is less than 0.06, the initial coulombic efficiency of the lithium ion battery is relatively low, severe lithium precipitation occurs (see FIG. 5), the cycle capacity retention rate is very low, and the cycle expansion rate is very high.

[0128] As shown in Examples 1 to 36, when the ratio Gr / K of the graphitization degree Gr of the negative electrode active material to K is in the range of 6 to 16 and K is in the range of 0.06 to 0.15, the initial coulombic efficiency and cycle capacity retention rate of the lithium ion battery can be significantly increased, the cycle expansion rate of the lithium ion battery can be significantly decreased, and the lithium precipitation phenomenon during the cycle of the lithium ion battery can be significantly reduced (see FIG. 3). The significant increase in the initial coulombic efficiency indicates that the energy density of the lithium ion battery is significantly increased. The significant increase in the cycle capacity retention rate and the significant decrease in the cycle expansion rate indicate that the cycle characteristics of the lithium ion battery are significantly improved. The improvement in the lithium precipitation phenomenon contributes to a significant increase in the rate characteristics of the lithium ion battery. Therefore, the lithium ion batteries of Examples 1 to 36 have significantly improved energy density, cycle characteristics, and rate characteristics.

[0129] When the graphitization degree Gr of the negative electrode active material is within the range of 0.92 to 0.96, the overall characteristics are more excellent.

[0130] In the negative electrode active material, when the crystallite size of the carbon material and the degree of orientation of the negative electrode active material satisfy the following relationship: Lc / S<9, La / S>20, Lc<45 and La>50, the initial coulombic efficiency, cycle capacity retention rate, cycle expansion rate and / or lithium precipitation phenomenon of the lithium ion battery can be further improved, and the overall properties of the lithium ion battery can be improved.

[0131] When Dv90 / Dv10+Dv90 is greater than 23.0, the cycle capacity retention rate and lithium precipitation phenomenon of the lithium ion battery are further improved, which contributes to improving the overall characteristics of the lithium ion battery.

[0132] FIG. 1 shows a scanning electron microscope (SEM) image of the negative electrode active material used in Comparative Example 2, magnified 500 times. As shown in the figure, the negative electrode active material of Comparative Example 2 contains only primary particles. FIG. 2 shows a scanning electron microscope (SEM) image of the negative electrode active material used in Example 5, magnified 500 times. As shown in the figure, the negative electrode active material of Example 5 contains primary particles and secondary particles at a certain ratio, and by adjusting the ratio between them, the graphitization degree and K value of the carbon material can be adjusted.

[0133] FIG. 6 shows a curve showing the relationship between the number of cycles and the cycle capacity retention rate at 25° C. for the lithium ion batteries in Comparative Example 1, Comparative Example 2, and Example 5. FIG. 7 shows a curve showing the relationship between the number of cycles and the cycle capacity retention rate at 45° C. for the lithium ion batteries in Comparative Example 1, Comparative Example 2, and Example 5. From the results, it can be seen that the lithium ion battery in Example 5 maintains a cycle capacity retention rate of 90% or more at 25° C. and 45° C., compared with Comparative Examples 1 and 2. With the increase in the number of cycles, the difference in the cycle capacity retention rate between Example 5 and Comparative Examples 1 and 2 gradually increases. FIG. 8 shows a curve showing the relationship between the number of cycles and the cycle expansion rate at 25° C. for the lithium ion batteries in Comparative Example 1, Comparative Example 2, and Example 5. FIG. 9 shows a curve showing the relationship between the number of cycles and the cycle expansion rate at 45° C. for the lithium ion batteries in Comparative Example 1, Comparative Example 2, and Example 5. From the results, it can be seen that the lithium ion battery in Example 5 has a cycle expansion rate of less than 8% at 25° C. and a cycle expansion rate of less than 10% at 45° C., compared with Comparative Examples 1 and 2. With the increase of cycle number, the difference in cycle expansion rate between Example 5 and Comparative Examples 1 and 2 gradually increases. From the above results, it can be seen that the lithium ion battery of Example 5 has significantly improved cycle performance during cycles at room temperature and high temperature.

[0134] Table 2 shows the effect of the properties of the negative electrode active material on the performance of the lithium ion battery. Examples 37 to 44 are examples of improvements over Example 5 in Table 1, and the only differences are the parameters listed in Table 2.

[0135] The results show that when the areal density of the negative active material layer is fixed, the overall performance of the battery can be affected by the compression density of the negative active material layer, the isotropy (S' reduction) of the negative active material layer, the porosity, and the peel strength between the negative active material layer and the negative current collector. 2 ~0.121mg / mm 2 and a compressed density of 1.70 g / cm 3 ~1.92g / cm 3When the S' of the lithium ion battery in a fully discharged state is 10 to 20, the peel strength between the negative electrode active material layer and the negative electrode current collector is 6 N / m to 15 N / m, the porosity of the negative electrode active material layer is 20% to 40%, the thermal decomposition temperature of the negative electrode active material layer in a fully charged state is 280°C or higher, and / or the thermal decomposition temperature of the negative electrode active material layer in a fully discharged state is 130°C or higher, the initial coulombic efficiency, cycle capacity retention rate, cycle expansion rate, and / or lithium precipitation phenomenon of the lithium ion battery are further improved, thereby improving the overall characteristics of the lithium ion battery. When the compressed density of the negative electrode active material layer is fixed, the areal density of the negative electrode active material layer is 0.100 mg / mm 2 Lithium ion batteries have relatively good overall characteristics.

[0136] Throughout the specification, references to "an embodiment," "partial embodiment," "one embodiment," "another example," "example," "embodiment," or "partial example" mean that at least one embodiment or example of the invention includes the particular feature, structure, material, or characteristic described in that embodiment or example. Thus, the appearances of, for example, "in some embodiments," "in an embodiment," "in one embodiment," "in another example," "in one example," "in a particular example," or "example" in various places throughout the specification do not necessarily refer to the same embodiment or example of the invention. Furthermore, particular features, structures, materials, or characteristics herein may be combined in any suitable manner in one or more embodiments or examples.

[0137] Although illustrative embodiments have been disclosed and described, those skilled in the art should understand that the above-described embodiments are not to be construed as limiting the present invention, and that changes, substitutions, and alterations to the embodiments are possible without departing from the spirit, principle, and scope of the present invention.

[0138] [Table 1]

[0139]

Table 2

Claims

1. A negative electrode active material containing a carbon material, The carbon material satisfies the relationship: 6<Gr / K<16, Gr is the graphitization degree of the carbon material measured by an X-ray diffraction method, and the Gr is 0.92 to 0.96; K is a ratio Id / Ig of a peak intensity Id of the carbon material at 1250 cm-1 to 1650 cm-1 and a peak intensity Ig of the carbon material at 1500 cm-1 to 1650 cm-1, both of which are measured by Raman spectroscopy; The carbon material satisfies the requirement that Lc is greater than 10 and not greater than 41.2, where Lc is a crystallite size along a vertical axis of a crystal of the carbon material measured by an X-ray diffraction method, and is expressed in nm; and The negative electrode active material has a Dv10 value and a Dv90 value that satisfy the following relationship: Dv90 / Dv10+Dv90>23.0, and the units of Dv90 and Dv10 are μm.

2. 2. The negative electrode active material according to claim 1, wherein K is 0.06 to 0.

15.

3. The carbon material satisfies at least one of the following relationships: Lc / S<9, La / S>20, however, La is the crystallite size along the horizontal axis of the crystal of the carbon material measured by X-ray diffraction, and is expressed in nm; S is the ratio of the peak area C004 of the (004) plane of the negative electrode active material obtained by measuring the X-ray diffraction pattern to the peak area C110 of the (110) plane, The negative electrode active material according to claim 1 , wherein Lc is greater than 10 and is equal to or less than 41.2, and La is greater than 50.

4. An electrochemical device comprising a positive electrode, an electrolyte, and a negative electrode, the negative electrode includes a negative electrode active material layer and a negative electrode current collector, The negative electrode active material layer comprises the negative electrode active material according to any one of claims 1 to 3.

5. The surface density of the negative electrode active material layer is 0.077 mg / mm2 to 0.121 mg / mm2, 5. The electrochemical device according to claim 4, wherein the compressed density of the negative electrode active material layer is 1.70 g / cm3 to 1.92 g / cm3.

6. 5. The electrochemical device according to claim 4, wherein a ratio S' of a peak area C004' of the (004) plane of the negative electrode active material layer to a peak area C110' of the (110) plane of the negative electrode active material layer obtained by measuring the X-ray diffraction pattern in a fully discharged state is within a range of 10 to 20.

7. 5. The electrochemical device according to claim 4, wherein a peel strength between the negative electrode active material layer and the negative electrode current collector is 6 N / m to 15 N / m.

8. The electrochemical device of claim 4 , wherein the negative electrode active material layer has a porosity of 20% to 40%.

9. 5. The electrochemical device according to claim 4, wherein the thermal decomposition temperature of the negative electrode active material layer is 280° C. or higher when the electrochemical device is in a fully charged state.

10. 5. The electrochemical device according to claim 4, wherein the thermal decomposition temperature of the negative electrode active material layer is 130° C. or higher when the electrochemical device is in a fully discharged state.

11. An electronic device comprising an electrochemical device according to any one of claims 4 to 10.

Citation Information

Patent Citations

  • Lithium ion battery negative electrode active material, lithium ion battery negative electrode, lithium ion battery, battery pack and battery power vehicle

    CN109553080A

  • Lithium ion battery negative electrode active material, lithium ion battery negative electrode, lithium ion battery, battery pack and battery power vehicle

    CN109553085A

  • All-solid-state battery

    WO2014016907A1